Mengolah Singkong Menjadi Kue Lapis Legit Desa Runding Mengolah Singkong menjadi kue - Robiatul Adawiah Rangkuty; Herman Syaputra Pasaribu; Samakmur Samakmur; Nur Aidah Siregar (Institut Pendidikan Tapanuli Selatan, 2022)
Freshwater cassava is one of the aquaculture commodities that is economically viable. Hutaimbaru is one of the villages in the Hutaimbaru sub-district where most of the residents have freshwater cassava ponds either for hobbies or additional income, therefore students are encouraged to carry out PKM activities in this village to develop freshwater cassava farming in this village. The objectives of this PKM are (1) to know what freshwater cassava farming is (2) to know how to cultivate freshwater cassava in a narrow area of ​​hutaimbaru village (3) to know the positive impact of freshwater cassava farming in the hutaimbaru village. The data collection technique used includes observation and documentation, the method used in its implementation is the Participatory Rural Appraisal method, which is an approach method that invites the community to participate in the development of activities. The results achieved from this PKM activity are increasing and developing interest and pote nsi of the community in freshwater cassava farming activities, as well as the realization of the image and development of freshwater cassava farming in improving the economy of the surrounding community. Keywords : Managing cassava into a legit layer cake, Runding Village Abstrak Singkong merupakan salah satu komoditas perkebunan manfaat yang bernilai ekonomis.Runding adalah salah satu desa di kecamatan panyabungan barat yang sebagian besar penduduknya memiliki lahan baik untuksekedar hobi atau tambahan dari penghasilan,oleh karena itu mahasiwa terdorong untuk melakukan kegiatan Pkm pada desa ini untuk mengembangkan manfaat singkong pada desa ini.Adapun Tujuan Pkm ini yaitu (1) mengetahui apa itu manfaat singkong (2) Mengetahui bagaimana cara memanfaatkan singkong dilahan sempit desa runding (3) mengetahui dampak positif dari budidaya singkong dilahan sempit desa Runding.Teknik pengumpulan data yang digunakan meliputi observasi dan dokumentasi,metode yang digunakan dalam pelaksanaannya adalah metode model Participatory Rural Apraissal yaitu suatu metode pendekatan yang mengajak masyarakat untuk turut berpartisipasi pada pengembangan kegiatan yang dilaksanakan.Hasil yang dicapai dari kegiatan Pkm ini yaitu meningkat dan berkembangnya minat dan potensi masyarakat dalam kegiatan manfaat singkong,serta terwujudnya citra dan berkembangnya memanfaatkan singkong dalam meningkatkan perekonomian masyarakat sekitar. Kata Kunci : Mengolah Singkong menjadi kue lapis legit